Designing Reading Material Based On Graha Bunda Maria Annai Velangkanni - Yenita br Sembiring; Berliana br Ginting; Susi Sandriani; Tabita Claudia Marcella Sianipar; Stevany Immanuella br Sinurat; Ira Maria Fran Lumbanbatu (PT FORMOSA CENDEKIA GLOBAL, 2024)
Graha Bunda Maria Annai Velangkanni is a spiritual tourist attraction where researchers carry out observations or research to obtain accurate information regarding the description of the building. This research at Graha Bunda Maria Annai Velangkanni aims to attract the reading interest of every reader, especially students, in terms of reading and understanding a text. This unique building object was used as a descriptive reading text that describes the unique shape, color or motif of the Graha Bunda Maria Annai Velangkanni building. The research method used in this research is qualitative descriptive, the aim is for readers to focus on observations made directly at Mother Annai Velangkanni's house. This research was carried out for three days and went through three stages, namely going around looking at the building, observing details of the shape of the building, and finally conducting interviews with sources, in order to get information about the building. Researchers found that the Graha Bunda Maria Annai Velangkani building is a unique and large building. The design combines Hinduism and Islam. In total there are two main floors of this building. Initially the purpose of this building was as a place for Catholics to pray in peace, but it turns out that all groups from various religions and languages can visit this building while still upholding a sense of tolerance between religious communities. From the results of research conducted by researchers, it can be concluded that reading materials based on Graha Bunda Maria Annai Velangkanni can increase interest in reading for many people, especially students